2012
DOI: 10.1186/1471-2229-12-238
|View full text |Cite
|
Sign up to set email alerts
|

A Tourist-like MITE insertion in the upstream region of the BnFLC.A10 gene is associated with vernalization requirement in rapeseed (Brassica napus L.)

Abstract: BackgroundRapeseed (Brassica napus L.) has spring and winter genotypes adapted to different growing seasons. Winter genotypes do not flower before the onset of winter, thus leading to a longer vegetative growth period that promotes the accumulation and allocation of more resources to seed production. The development of winter genotypes enabled the rapeseed to spread rapidly from southern to northern Europe and other temperate regions of the world. The molecular basis underlying the evolutionary transition from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(105 citation statements)
references
References 54 publications
7
96
0
2
Order By: Relevance
“…It is perhaps unsurprising, then, that Table 2 reveals a wide diversity in the nature of the mutations that underlie domestication-related phenotypes. These include cis -regulatory mutations that increase gene expression (e.g., rapeseed BnFLC.A10 , controlling vernalization; Hou et al, 2012), and mutations in coding regions that result in modified proteins that remain functional but have altered activity (e.g., sunflower HaFT1 , controlling flowering time; Blackman et al, 2010). The largest proportion of these domestication-related genetic changes, however, are those that result in a loss of gene function.…”
Section: Genetic Basis Of Domestication Phenotypesmentioning
confidence: 99%
See 2 more Smart Citations
“…It is perhaps unsurprising, then, that Table 2 reveals a wide diversity in the nature of the mutations that underlie domestication-related phenotypes. These include cis -regulatory mutations that increase gene expression (e.g., rapeseed BnFLC.A10 , controlling vernalization; Hou et al, 2012), and mutations in coding regions that result in modified proteins that remain functional but have altered activity (e.g., sunflower HaFT1 , controlling flowering time; Blackman et al, 2010). The largest proportion of these domestication-related genetic changes, however, are those that result in a loss of gene function.…”
Section: Genetic Basis Of Domestication Phenotypesmentioning
confidence: 99%
“…In this case, exposure of ripening fruits to cold induces retrotransposon-mediated transcriptional activation of Ruby , a Myb regulatory gene in the anthocyanin synthesis pathway (Butelli et al, 2012). Other domestication-related traits that have evolved through TE activity include determinate growth in common bean ( PvTFL1y ; Repinski et al, 2012); vernalization requirement in rapeseed ( BnFLC.A10 ; Hou et al, 2012) and wheat ( Vrn1 ; Golovnina et al, 2010); and photoperiod sensitivity in rice ( Ehd1 ; Saito et al, 2009). …”
Section: Genetic Basis Of Domestication Phenotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…In B. napus , a Tourist -like MITE, Monkey King , was identified in the promoter region of BnFLC.A10 , a homologue of Arabidopsis FLOWERING LOCUS C ( FLC ) [31]. In this study, we found that Monkey King elements are not restricted to Brassica species, but are specific to the Brassicaceae family.…”
Section: Introductionmentioning
confidence: 78%
“…Association and QTL mapping studies have also associated variation in flowering time or vernalization response with polymorphisms in the FLC homologs of Brassica oleracea, Brassica rapa, and Brassica napus (Zhao et al, 2010;Hou et al, 2012;Wu et al, 2012;Irwin et al, 2016). For instance, one of two major FLC haplotypes in B. oleracea is transcriptionally repressed by cold exposure more slowly than the other (Irwin et al, 2016).…”
Section: Diversity In How Long Winter Needs To Be Experiencedmentioning
confidence: 99%